2017
DOI: 10.1152/ajpgi.00142.2017
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and mechanisms of the supragastric belch in the cat

Abstract: A response in which a belch occurs without gastric involvement, i.e., the supragastric belch (SGB), has been characterized in humans. The aims of this study were to determine whether animals have an SGB and, if so, to determine its mechanisms. Studies were conducted in decerebrate cats ( = 30) with electromyographic electrodes on hyoid, pharyngeal, esophageal, and diaphragm muscles. The effects of distending different regions of the esophagus in different manners using a balloon were quantified to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 29 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…In such cases, stressful life events might precipitate SBG. In animal experiments, Lang et al found that esophageal distension can trigger a reflex of inhaling air followed by belching via vagal nerves and esophageal tension/mucosal mechanoreceptors [ 15 ]. In light of this finding, a limited part of SGB might be a reflex rather than a behavior, especially when gas reflux causes the initial esophageal distension.…”
Section: Two Types Of Belching: Gastric Belching and Supragastric mentioning
confidence: 99%
“…In such cases, stressful life events might precipitate SBG. In animal experiments, Lang et al found that esophageal distension can trigger a reflex of inhaling air followed by belching via vagal nerves and esophageal tension/mucosal mechanoreceptors [ 15 ]. In light of this finding, a limited part of SGB might be a reflex rather than a behavior, especially when gas reflux causes the initial esophageal distension.…”
Section: Two Types Of Belching: Gastric Belching and Supragastric mentioning
confidence: 99%
“…The thoracic esophagus showed greater sensitivity to this reflex response than the cervical esophagus, and this response was sensitized by the exposure of the esophagus to acids [56]. All subreflexes of the SGB were blocked by vagotomy [56]. Local anesthesia of the esophageal mucosa blocked EURR, but could not trigger reflex activation of inhalation [56].…”
Section: Functionmentioning
confidence: 98%
“…Initially, it was thought that this was a voluntary response [53][54][55], but recent studies [49] suggest that this may be a learned reflex response. It was observed in studies on decerebrate cats that rapid distention of the esophagus with a balloon could trigger an inhalation response that is immediately followed by activation of the EURR and release of air out of the esophagus and mouth [56]. The thoracic esophagus showed greater sensitivity to this reflex response than the cervical esophagus, and this response was sensitized by the exposure of the esophagus to acids [56].…”
Section: Functionmentioning
confidence: 99%
See 2 more Smart Citations